Analysis of Sharia Law in The Management of Sales at Gas Station Mini Pertalite (Case Study in Mlarak Small Public Gas Stations) - Annas Syams Rizal Fahmi; May Shinta Retnowati; Emha Afifudzaki Anwar (Universitas Darusssalam Gontor, 2018)
Opportunities to sell Fuel (BBM), especially pertalite in Mlarak sub-district, are getting easier and faster with the help of new machines distributed to several corners of the village. Similar to General Gas stations, sales are made using dispenser machines, the amount of volume and price are clearly exposed on the display boards. However, there are still acts of some persons in Small Gas Station that do not heed the Islamic norms in sales, ie do not sell fuel oil does not match the dosage that should be. Though the right dose that has been agreed in the contract is a legal requirement for selling and buying, so the sale is included in the category of gharar. From the results of this study, it can be concluded that there is still a mini gas station in Mlarak sub-district that cheats the actual dosage, this indicates the practice of Trading contains elements of gharar and haram law in Islam, because it harms the consumer. With this research, it is expected to make the society especially the seller of Pertalite at Small Gas Station aware of the form of Trading they do, because every relationship with human not only to seek personal gain, but also to bring benefit and goodness to others.